An Early Neogene—Early Quaternary Contourite Drift System on the SW Barents Sea Continental Margin, Norwegian Arctic. (30th October 2020) - Rydningen, T. A.; Høgseth, G. V.; Lasabuda, A. P. E.; Laberg, J. S.; Safronova, P. A.; Forwick, M.
Abstract: The onset and evolution of the middle to late Cenozoic "icehouse" world was influenced by the development of the global ocean circulation linking the Norwegian–Greenland Sea‐Arctic Ocean to the Atlantic Ocean. The evolution of the early Neogene to early Quaternary Bjørnøyrenna Drift, located at the SW Barents Sea continental margin, shed new light on this important hydrological event. By analyzing seismic data and exploration wellbores, it is found that the drift likely started to form in the early/middle Miocene, probably as a result of an ocean circulation reorganization following the opening of the Fram Strait gateway (c. 17 Ma) and subsidence of the Greenland–Scotland Ridge (c. 12 Ma). Thus, the onset of drift growth is considered to have happened close in time to the Mid Miocene Climatic Optimum at 16–14 Ma, and was part of a regional onset of large‐scale ocean circulation in the Norwegian–Greenland Sea that influenced the subsequent climate cooling. The drift continued to grow under the influence of early Quaternary glacimarine sedimentation, and later overtopping of the drift mound by downslope transfer of glacigenic sediments during full‐glacial conditions resulted in a submarine failure. For the first time, minimum average sedimentation rates of a Neogene to Quaternary drift in this area is calculated, giving rates of 0.020–0.031 m/Kyr. These values are comparable to average deep‐sea sedimentation rates from modern low‐latitude river systems such as the Amazon and Mississippi, but lower than the Quaternary glacial sedimentation rates from the Barents Sea and Fennoscandian continental margins. Plain Language Summary: The ocean water masses are constantly moving through the thermohaline circulation, which both distribute heat from low to high latitudes, as well as cold water in the opposite direction. This is crucial for maintaining the global climate, and the start and evolution of ocean currents can be decrypted from marine sedimentary deposits known as contourite drifts. This study outlines the evolution of a drift that likely started building up in the SW Barents Sea when the Gulf Stream first extended into the Arctic Ocean. This likely happened as important ocean passages such as the Fram Strait gateway west of Svalbard opened up, which occurred during a global temperature highpoint in the mid Miocene (16–14 Ma). The global temperatures dropped following this, possibly partly because of the establishment of this ocean circulation, allowing for precipitation and growth of larger ice caps on the northern hemisphere. The drift accumulated by 0.020–0.031 m per 1, 000 years, before it was later rapidly buried (at a rate of 0.18–0.64 m per 1, 000 years) by glacigenic sediments during the last 2.7 Ma. The weight of these overlying sediments likely caused parts of the drift to fail, resulting in a large submarine slide. Key Points: The Bjørnøyrenna Drift records the high north ocean circulation that influenced climate deterioration after the Mid Miocene Climatic Optimum The drift accumulated on the slope until Quaternary glacigenic sediments buried it, resulting in a submarine failure The drift sedimentation rates compare to deep‐sea input from the Amazon/Mississippi rivers, but are less than from continental ice caps